Ophiopogonin D: review of pharmacological activity - Chen, Ke-qian; Wang, Shu-zhi; Lei, Hai-bo; Liu, Xiang (Frontiers in Pharmacology, 2024)
Background: Ophiopogon D is an important natural organic compound in Ophiopogon japonicus, which often has significant biological activity.The purpose of this review is to systemically summarize and discuss the pharmacological activity and underlying mechanisms of OP-D in recent years.Method: PubMed and Web of Science were searched with the keywords:"Ophiopogon japonicus", "Ophiopogon D" "pharmacology", and "pharmacokinetics". There was no restriction on the publication year, and the last search was conducted on Jan 1, 2024.Results: Emerging evidence suggests that OP-D possess numerous pharmacological activities, including bone protection, cardiovascular protection, immune regulation, anti-cancer, anti-atherosclerosis, anti-inflammatory and anti-NAFLD.OP-D has a potential value in the prevention and treatment of many diseases. We hope that this review will contribute to therapeutic development and future studies of OP-D.